2013
DOI: 10.1155/2013/920713
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in Individual Retinal Layers in Diabetic Macular Edema

Abstract: Optical coherence tomography (OCT) has enabled objective measurement of the total retinal thickness in diabetic macular edema (DME). The central retinal thickness is correlated modestly with visual impairment and changes paradoxically after treatments compared to the visual acuity. This suggests the clinical relevance of the central retinal thickness in DME and the presence of other factors that affect visual disturbance. Recent advances in spectral-domain (SD) OCT have provided better delineation of the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 82 publications
(81 reference statements)
2
89
0
2
Order By: Relevance
“…In a report of cases with both branch retinal vein occlusion and DME, serous macular detachment was shown to be a negative prognostic factor for anatomical improvement [13]. Structural analysis of individual retinal layers in the literature has concluded that eyes with foveal serous macular detachment tend to have a poorer prognosis regarding visual function [14]. Yaya et al [15] found serous macular detachment in 52.4% of 143 eyes and associated it with systemic hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…In a report of cases with both branch retinal vein occlusion and DME, serous macular detachment was shown to be a negative prognostic factor for anatomical improvement [13]. Structural analysis of individual retinal layers in the literature has concluded that eyes with foveal serous macular detachment tend to have a poorer prognosis regarding visual function [14]. Yaya et al [15] found serous macular detachment in 52.4% of 143 eyes and associated it with systemic hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…However, we should note that the concept of ERI does not mean a complete restoration of high-resolution images without additional image information but image enhancement. We believe that the ERI method is useful as a type of display format in the analysis of fine structures in OCT images such as hyper-reflective foci [31,32,33,37], the retinal nerve fiber layer near the fovea [38,39], intricately affected photoreceptor layers [40,41], and vessels [42,43]. Further, MBP as well as IBP suffer from the drawback of noise enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…In opposition, the SRD and DRT edemas typically start manifesting in the outer retina. In more severe pathological stages, the CMEs could proliferate from the inner retina to the outer retina and merge with the DRT edemas [96,97]. Based on that premises, two sub-regions are identified inside the ROI as the inner and outer retina, using the previously identified layers.…”
Section: Division Of the Roi In Two Sub-regions: Inner And Outer Retinamentioning
confidence: 99%
“…Their morphology could vary from a honeycomb shape to a petaloid-like appearance (like petals of the flowers) [96]. This edema typically emerges in the inner retina with a significant contrast with the surrounded tissue.…”
Section: Cme Detectionmentioning
confidence: 99%